Miniaturization of breath sampling with silicon chip: application to volatile tobacco markers tracking. (12th September 2018) - Chappuis, Thomas Hector; Pham Ho, Bao An; Ceillier, Morgan; Ricoul, Florence; Alessio, Manuel; Beche, Jean-Francois; Corne, Christelle; Besson, Gérard; Vial, Jérôme; Thiébaut, Didier; Bourlon, Bertrand
Abstract: This work presents the performances of silicon micro-preconcentrators chips for breath sampling. The silicon chips were coupled to a handheld battery powered system for breath sampling and direct injection in a laboratory gas chromatography mass spectrometry system through thermal desorption (TD). Performances of micro-preconcentrators were first compared to commercial TD for benzene trapping. Similar chromatographic peaks after gas chromatographic separation were observed while the volume of sample needed was reduced by a factor of 5. Repeatability and day to day variability of the micro-preconcentrators were then studied for a 500 ppb synthetic model mixture injected three times a day four days in a row: 8% and 12% were measured respectively. Micro-preconcentrator to micro-preconcentrator variability was not significant compared to day to day variability. In addition, micro-preconcentrators were tested for breath samples collected in Tedlar ® bags. Three analyses of the same breath sample displayed relative standard deviations values below 16% for eight of the ten most intense peaks. Finally, the performances of micro-preconcentrators for breath sampling on a single expiration were illustrated with the example of volatile tobacco markers tracking. The signals of three smoking markers in breath, benzene, 2, 5-dimethylfuran, and toluene were studied. Concentrations of benzene and toluene were found to be 10 to 100 higher in the breath of smokers. 2, 5-dimethylfuran was only found in the breath of smokers. The elimination kinetics of the markers were followed as well during 4 h: a fast decrease of the signal of the three markers in breath was observed 20 min after smoking in good agreement with what is described in the literature. Those results demonstrate the efficiency of silicon chips for breath sampling, compared to the state of the art techniques. Thanks to miniaturization and lower sample volumes needed, micro-preconcentrators could be in the future a key technology towards portable breath sampling and analysis.